Prediction on the solidification behavior of AA6005 aluminum alloys produced by inclined twin-roll casting: A finite element analysis - Xu Liu; Jia-Wang Song; Xuan Wang; Zhi-Gang Li; Shao-You Zhang; Wei-Tao Jia; Cheng Wang; Hui-Yuan Wang (Journal of Materials Research and Technology, 2024)
Conventional horizontal twin-roll casting (TRC) with steel rollers generally possesses slow casting speed. In this study, the inclined TRC method with Cu rollers was proposed, which significantly increases the casting efficiency. A three-dimensional model of the inclined TRC was established, which revealed the temperature field, solid fraction, velocity distribution, and TRC microstructure of the AA6005 aluminum (Al) alloys by the finite element simulation. We considered the various effects of the pouring temperature, roll gap, and rolling speed on the outlet temperature of the inclined cast rolling zone, and determined the appropriate range of processing parameters. The casting speed of the inclined TRC process could reach ∼5.8–7.9 m/min when the roll gap was 2 and 3 mm. Due to the different contact areas between the melt and two rollers, the temperature field and the shape of the liquid hole were asymmetric, and the isotherm and solidification end point (Kiss point) shifted to the direction of the upper roller at the steady inclined TRC state. The columnar/equiaxed grain structure and the upper shift of central segregation in the inclined TRC sheets were successfully simulated by the finite element method, which was in good agreement with the experiments. Moreover, the inclined TRC method with Cu rollers has high cooling intensity and the potential to eliminate central segregation. The results of this study can effectively reduce the trial-and-error effort, and provide a new insight into the development of the TRC Al alloys.